Serum Levels of Antioxidant Vitamins (Vitamin A, C, E) and Magnesium in Children with Allergic Rhinitis - Sancak, R. (Aves Yayincilik, Ibrahim Kara, 2010)
Objectives: The aim of the study is to measure the levels of antioxidant vitamins and magnesium during allergic rhinitis attacks. Patients and Methods: Thirty five children who have sensitivity for house dust and mite with mild/ moderate persistent allergic rhinitis without any other allergic diseases were considered as the study group, and 35 healthy children as the control group. The patient group was classified accord- ing to the symptom scoring system. Venous blood samples were obtained before breakfast in each group to determine serum vitamin A, C, E and magnesium levels. Results: Serum vitamin A level was significantly lower in the study group compared with the control group. However, there was no statistically sig- nificant difference between the groups in terms of serum vitamin C, E and magnesium levels. Conclusion: This study showed that vitamin A consumption increases to repair mucosal epithe- lium which is damaged by inflammation and to prevent the oxidative damage in allergic rhinitis. This result may imply new therapeutic approaches. © Medical Journal of Trakya University.
Allerjik Rinitli Çocuklarda Antioksidan Vitaminler (Vitamin A, C, E) ve Magnezyum Düzeyleri
Keywords: Allergic Rhinitis; Child; Free Radicals; Magnesium; Oxidative Stress; Vitamin A; Vitamin C; Vitamin E